Odpowiedź :
Odpowiedź:
a) 14+28+[tex]14\sqrt{3}[/tex] = 42+[tex]14\sqrt{3}[/tex]
b) 1+1[tex]\sqrt{3}[/tex]+[tex]\sqrt{2} + \sqrt{2}[/tex] = 1+1[tex]\sqrt{3}[/tex]+2[tex]\sqrt{2}[/tex]
c) 7 + 7[tex]\sqrt{3}[/tex] +14[tex]\sqrt{2}[/tex]+14=21+7[tex]\sqrt{3}[/tex]+14[tex]\sqrt{2}[/tex]
Mam nadzieję, że dobrze i liczę na naj :D
Odpowiedź:
[tex]a) 14+28+14\sqrt{3} =42+14\sqrt{3} \\b) 1+1\sqrt{3} +\sqrt{2} +\sqrt{2} =1+1\sqrt{3} +2\sqrt{2} \\c) 7+7\sqrt{3} +14\sqrt{2} +14=21+7\sqrt{3}+14\sqrt{2}[/tex]